Effect of voltage-gated calcium channel beta anchoring and regulating protein deletion on insulin secretion in glucose intolerant C57BL/6 mice. - Tang, Fengxiang. (2012)
BARP which is endogenously expressed in insulin-secreting cells was found to modulate calcium-dependent secretion through VGCC downregulation. However, little was done to determine the effects of BARP on insulin secretion. Therefore, in addition to previous work on BARP overexpression studies, 12-14-week-old C57BL/6 mice of pancreas-specific BARP knockout (P-BARP-KO) were used here to study the effect of BARP deletion on insulin secretion. Cre recombinase mediated the removal of BARP sequence between loxP sites in P-BARP-KO mice. Effect of BARP deletion was first studied at the systemic level via IPGTT and non-fasting blood tests. P-BARP-KO mice were observed to be glucose intolerant with reduced insulin secretion. Further IPITT analysis dismissed the possibility of insulin insensitivity in P-BARP-KO mice. ELISA measurements of islet insulin content suggested a decrease in insulin production in P-BARP-KO mice. The effect of BARP deletion on islet development was further analyzed through histological observations. General islet architecture of the P-BARP-KO mice appeared normal although morphometric determinations detected reduced β-cell count and β-cell hypertrophy. Therefore, P-BARP-KO mice had reduced plasma insulin with concomitant β-cell changes. Summarizing the previous findings with the current study has shown BARP to assume a regulatory function instead of an essential role in calcium-mediated hormone release.